KAJIAN ADVOCATE SEBAGAI TAHAPAN PEMASARAN FILM DOKUMENTER â€œEKSILâ€ - Zanetta Charissa Eliezer Bangun; Firmanda Satria; Alvanov Zpalanzani Mansoor (Cinelook: Journal of Film, Television, and New Media, 2025)
During the past 2024 general election of Indonesia, the public got encouraged to find out more about Indonesian politics, especially about sensitive Indonesian history. One of the mediums used to show history more effectively is historical documentary films. A historical documentary film which was recently released and went viral in early 2024 is â€œEksilâ€, a film about the testimonies of Indonesian students who were exiled to European countries in 1965â€”1966 because of their disagreement towards the New Order. Because the film contains sensitive Indonesian history, the film crew of â€œEksilâ€ didnâ€™t carry out extensive marketing and limited screenings of the film. The film crew and the audience mainly uses X and Instagram to market the film, especially using testimonies. Therefore, they unconsciously apply the 5A Marketing Model, primarily applying the advocate stage. This research is done to learn about how the film crew and the audience applied the advocate stage of the 5A Marketing Model to market â€œEksilâ€. Â Data is collected by collecting screenshots of X and Instagram posts of testimonies regarding the film and mapping them based on time, which are before, during, and after the release of the film in cinemas using content analysis and descriptive qualitative methods. The results show that the application of the advocate stage of the 5A Marketing Model made the public gain interest on watching the film with sixty thousand viewers garnered after 1,5 months of release in cinemas and the marketing isnâ€™t centralized and spread separately, but is continuous from one account to another regardless of influence.